Training the Trainers: Towards a Description of Translator Trainer Competence and Training Needs Analysis - Kelly, Dorothy (TTR, 2008)
AbstractThere is now a relative wealth of Translation Studies literature on translator training, but it often centres on impersonal aspects such as processes, content or activities, and ignores the human factor. There are two sets of participants in the teaching and learning process, both of whom are essential for its success: students or trainees, and teachers or trainers. Other than to bemoan their supposed deficiencies, or to design elaborate entrance filters, little has been said about students. But even less has been said about trainers. In this paper, attention focuses on them. The little that TS literature says about trainer profiles is mostly centred on the need for them to have professional translator competence. This paper takes a broader approach to the issues surrounding translator trainers and their training, setting them firmly within the broader context of higher education teaching as a profession, and attempts to link recently developed professional standards in higher education teaching to our field. This background allows the author to draw up a competence-based profile of the translator trainer and briefly to review which areas of such a profile have been addressed in TS and which are still in need of further work. The paper ends with an overview of the preliminary results of a study currently underway in Spain, designed to carry out detailed training needs analysis for translator trainers.